EFFECT OF SEED INVIGORATION ON GROWTH, YIELD AND ECONOMICS OF SUNFLOWER (Helianthus annuus L.) - RUPA DAS,; SAIKAT BISWAS, (The Bioscan, 2021)
The study was conducted by treating various sized sunflower seeds with invigoration treatments to evaluate growth, yield and economics of the crop. Results revealed that seed invigoration with various powders improved growth and yield of sunflower over control or dry seeds. Specifically, large sized seeds treated with red chilli powder when sown in the field, produced highest plant growth (plant height, 113.90 cm), yield attributes (seed set, 84.27%) and consequently, seed yield (2439.87 kg ha -1 ), stalk yield (5316.84 kg ha -1 ), oil yield (1051.75 kg ha -1 ) and harvest index (31.44 %). However, crop grown from large sized seeds treated with bleaching powder exhibited statistically similar plant growth (plant height, 111.76 cm), yield attributes (seed set, 84.15 %) and thereby, seed yield (2390.77 kg ha -1 ), stalk yield (5280.87 kg ha -1 ), oil yield (1029.62 kg ha -1 ) and harvest index (31.16 %) as observed in large seeds treated with red chilli powder. In consequence of high yield, crops grown from large seeds showed high and statistically similar profitability when treated with either red chilli powder (net return, INR. 76,885.03 ha -1 ; B:C, 3.01) or bleaching powder (net return, INR. 74,643.36 ha -1 ; B:C, 2.95) and therefore, both these seed invigoration options can be recommended for ideal sunflower cultivation.